2013
DOI: 10.1371/journal.pone.0054523
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Mobility and the Risk of HIV Infection among Married Couples in the Fishing Communities along Lake Victoria, Kenya

Abstract: ObjectiveMobility has long been associated with high HIV prevalence. We sought to assess sex differences in the relationship between mobility and risk for HIV infection among married couples in the fishing communities.MethodsWe conducted 1090 gender-matched interviews and rapid HIV testing with 545 couples proportionally representing all the different sizes of the fish-landing beaches in Kisumu County. We contacted a random sample of fishermen as our index participants and asked them to enrol in the study toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 35 publications
4
95
3
Order By: Relevance
“…These patterns delineate mobile youth in Rakai as a group at especially high risk of HIV. Previous research has demonstrated elevated HIV risk and risk behaviours among mobile populations, though largely among adults (Anglewicz, 2012; Bärnighausen et al, 2007; Brockerhoff & Biddlecom, 1999; Goldenberg et al, 2012; Kwena, Camlin, Shisanya, Mwanzo, & Bukusi, 2013; Tiruneh, Wasie, & Gonzalez, 2015; Zuma et al, 2003). Female migrants have been described as a particularly vulnerable group (Brockerhoff & Biddlecom, 1999; Camlin et al, 2014; Temin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These patterns delineate mobile youth in Rakai as a group at especially high risk of HIV. Previous research has demonstrated elevated HIV risk and risk behaviours among mobile populations, though largely among adults (Anglewicz, 2012; Bärnighausen et al, 2007; Brockerhoff & Biddlecom, 1999; Goldenberg et al, 2012; Kwena, Camlin, Shisanya, Mwanzo, & Bukusi, 2013; Tiruneh, Wasie, & Gonzalez, 2015; Zuma et al, 2003). Female migrants have been described as a particularly vulnerable group (Brockerhoff & Biddlecom, 1999; Camlin et al, 2014; Temin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Kenya, Tanzania, Burkina Faso, Zimbabwe, South Africa and Cameroon have shown an association between increased mobility and increased levels of sexual behavior [1-3], increased risk of HIV infection [4, 5], or both [6-10]. These studies indicate population mobility may have a significant effect on HIV transmission in these countries.…”
Section: Introductionmentioning
confidence: 94%
“…In Uganda, over 2.5 million people are engaged in fishing as a means of gainful employment for unskilled workers such as fishermen, fish processors, traders and barmaids who often travel away from home for long periods, moving between temporary fishing camps [11]. This mobility has been linked to high risk sexual behaviour and bridges sexual networks into the general population [7]. Mobility could also pose a challenge to successful retention of individuals from fishing communities and it is not known if fishing communities can make a commitment to participate in trials.…”
Section: Introductionmentioning
confidence: 99%